2021
DOI: 10.1007/s00338-021-02158-y
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of a major reef-building coral species Acropora downingi in northeastern Arabian Peninsula

Abstract: Current seawater temperatures around the northeastern Arabian Peninsula resemble future global forecasts as temperatures > 35 °C are commonly observed in summer. To provide a more fundamental aim of understanding the structure of wild populations in extreme environmental conditions, we conducted a population genetic study of a widespread, regional endemic table coral species, Acropora downingi, across the northeastern Arabian Peninsula. A total of 63 samples were collected in the southern Arabian/Persian Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…However, a phylogeographical study of Periophthalmus waltoni , a marine amphibious fish with terrestrial adaptations, revealed two distinct genetic clusters, one represented by the Gulf individuals and the other by individuals from the Sea of Oman. Likewise, genetic investigations involving corals (Howells et al, 2016; Torquato et al, 2021) and sea urchin (Ketchum et al, 2020) showed a genetic discontinuity through the Strait of Hormuz. Indeed, biogeographical survey indicated higher levels of endemism for invertebrates within the Gulf compared to fishes (DiBattista, Roberts, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a phylogeographical study of Periophthalmus waltoni , a marine amphibious fish with terrestrial adaptations, revealed two distinct genetic clusters, one represented by the Gulf individuals and the other by individuals from the Sea of Oman. Likewise, genetic investigations involving corals (Howells et al, 2016; Torquato et al, 2021) and sea urchin (Ketchum et al, 2020) showed a genetic discontinuity through the Strait of Hormuz. Indeed, biogeographical survey indicated higher levels of endemism for invertebrates within the Gulf compared to fishes (DiBattista, Roberts, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with Acropora showed that its larval survival strongly declined after the first few days after spawning, with half‐life shorter than 5 days (Graham et al, 2008). Nevertheless, the population differentiation of P. daedalea and A. downingi through the Strait of Hormuz has also been explained by natural selection (Howells et al, 2016) and recent bottlenecks (Torquato et al, 2021), respectively. In turn, the sea urchin ( Echinometra sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations